Dietetics Prescribed in Ancient Ayurveda Correlated with Pediatrics Guideline of Dietetic Prescription for Severe Acute Malnutrition in Age of 6 Months to 60 Months - Chandra, K. Rama (Asian Journal of Pharmaceutics (AJP), 2023)
“India had been called the golden sparrow,” we have grown up listening to these lines since childhood, but today when we look at the figures of National Family Health Survey, World Health Organization, National Institute of Nutrition etc., it hurts a lot. Today, about 45% children of India fall in the stunted category. However, to fight malnutrition, a Nutrition Rehabilitation Centre has been established here in India, in which children are treated with therapeutic diet and if studies are to be believed, its results are also very good. After studying the traditional medical method of our India (Ayurveda), it was found that even from the Ayurvedic point of view, the elements of the therapeutic diet used in this center proved to be equally good and capable of fighting malnutrition. This diet has also proven to be appropriate and generally safe based on over 2000 years of Ayurvedic knowledge.